Effects of rubber inclusion on multiscale shear response of sand-geostructure interface - Ari, A.; Akbulut, S. (EMERALD GROUP PUBLISHING LTD, 2026)
This study investigates the effects of rubber particles on the interface shear response between sand and structural surface. Rubber particles were added in two ways: mixed with sand and placed directly on the surface as an intermediate layer. The interface scenarios were varied based on rubber content, rubber particle shape, and surface roughness form. A custom-made transparent shear box was fabricated to capture local deformations through digital image correlation analyses. Peak, residual shear strengths, and dilation angle were used to quantify the macro-scale response. Particle sliding percentage and shear band thickness were employed to characterize the meso scale response. Consequently, elongated rubber produced higher shear strength than crumb rubber; however, the dilation varied with the inclusion type of rubber. The on-surface rubber inclusion resulted in a more contractive response compared to the mixed-type condition. Limited rubber inclusion increased shear strength in the mixed type, while in the on-surface case, it varied with surface roughness. Sliding percentage increased with rubber content, while rubber inclusion resulted in thinner shear bands. Particle sliding and shear band thickness were controlled by the rubber shape, surface roughness, and type of rubber inclusion. The variations in macro-scale response were analyzed in relation to meso-scale parameters.
Keywords: Geosynthetics; & Idot; nterfaces; Shear; Rubber shape; Roughness form; Multiscale response; Rubber & Idot; nclusion; Macroscale response; Mesoscale response; DYNAMIC PROPERTIES; GRANULAR SOILS; BEHAVIOR; MIXTURES; STRENGTH; FAILURE; STATE; Engineering; Geology; Materials Science